Eco-friendly synthesis and catalytic activity of Cu nanoparticles deposited on expanded muscovite to reduce organic pollutants - Abduraboh Alraae; Ali Moussadik; Abdellah Benzaouak; Mohammed Kacimi; Mohammed Dahhou; Aicha Sifou; Adnane El Hamidi (Results in Surfaces and Interfaces)
Supported metal nanoparticles on various substrates have demonstrated high activity efficiency, resistance to aggregation, and ease of recyclability. In this study, the expansion of natural muscovite was investigated through a process involving acidic treatment followed by heat treatment (calcination). Afterward, muscovite-supported copper nanoparticles Cu(NPs)/MST was synthesized using a wet-chemical method and characterized by various techniques, such as Fourier transform infrared spectroscopy FT-IR, X-ray diffraction XRD, scanning electron microscopy SEM, energy dispersive spectroscopy EDX, and transmission electron microscopy TEM. Initially, the adsorption behavior of muscovite towards copper ions was examined, revealing optimal adsorption of copper ions at pH = 5.20 ± 0.12 with an adsorption capacity of 22.58 mg.mg−1. The subsequent reduction process using sodium borohydride (NaBH4) led to the formation of Cu nanoparticles with diameters ranging from 4 nm to 20 nm according to the TEM analysis. These nanoparticles exhibited high catalytic activity in the reduction of organic pollutants in less than 10 min with high reaction rate constants. The findings of this study underscore the potential of muscovite as a promising substrate for catalytic support. Further research is recommended to explore the expansion of muscovite through straightforward thermochemical treatments and its capability to host a wide range of catalyst species.